Autistic Children Are More Responsive to Tactile Sensory Stimulus - Asmika, Asmika; Oktafiani, Lirista; Kusworini, Kusworini; Sujuti, Hidayat; Andarini, Sri (Iranian Journal of Child Neurology, 2018)
Objective This research was an experimental study that was aimed to detect differences respon of Tactile Sensory Stimulus between normal children and children with sensory brain development disorders such as ASD (Autism Spectrum Disorder). Materials & Methods A total of 134 children, in two groups: 67 healthy children (control) and 67 children with autism were studied. Tactile sensory stimulus responses in children were tested directly using a Reflex Hammer. In addition, tactile sensory sensitivity was also assessed via questionnaire Short Sensory Profile (SSP) which was filled out by the child’s parents. All response data were analyzed using Fisher’s Exact Test; questionnaire data was analyzed with the Mann-Whitney U Test. Result The results showed that autistic children were more sensitive to palpation and pain than children who were not autistic. Furthermore, the value of SSP was also significantly higher in autistic children, which means that they always responded to all categories in the SSP questionnaire than children who are not autistic. Conclusion Autistic children are more sensitive to Tactile Sensory Stimulus and all categories of SSP than children who are not autistic.